Indigenous Knowledge, Community and Education in a Western System: An Integrative Approach - Overmars, Danika (First Peoples Child & Family Review, 2010)
Colonization attempted to eradicate Indigenous knowledge and Indigenous Ways of knowing through coerced education, yet education may be the key to the healing journey for Aboriginal people in Canada. At present the educational system is not serving Aboriginal students well as measured by levels of student success. The integration of Indigenous knowledge, community and education increases the likelihood of success of students in educational settings and promotes healing from colonization. Research suggests that a community based model of education is not only appropriate for Aboriginal students but is likely to enhance their education by providing community controlled and culturally relevant experiences.